Applications of Artificial Intelligence in Food Industry - Heera Jayan; Weiqing Min; Zhiming Guo (Foods)
With breakthroughs in artificial intelligence (AI) brought by the fourth industrial revolution, intelligent applications are providing innovative solutions across food industry [...]